PEMANFAATAN MEDIA AUDIO VISUAL SEBAGAI SUMBER PEMBELAJARAN SEJARAH - Ainina, Indah Ayu (Indonesian Journal of History Education, 2014)
The research problem is how to use audiovisual media in the teaching of history based on the history learning class XI student of High School 2 Holy Bae academic year 2013/2014, and is there any influence of audiovisual media utilization of teaching history to the learning outcomes of student learning outcomes in class XI of High School 2 Holy Bae academic year 2013/2014 the aim of this study was to examine the use of audiovisual media-based teaching history in learning history, to determine the class XI student learning outcomes, and the effect of the use of media-based audio-visual teaching history to the learning outcomes in the subjects of history class XI Social High School 2 Bae Kudus.Â Permasalahan dalam penelitian adalah bagaimana pemanfaatan media pembelajaran sejarah berbasis audiovisual dalam pembelajran sejarah pada siswa kelas XI SMA Negeri 2 Bae Kudus tahun ajaran 2013 / 2014, dan adakah pengaruh pemanfaatan media pembelajaran sejarah audiovisual terhadap hasil belajar hasil belajar siswa kelas XI SMA Negeri 2 Bae Kudus tahun ajaran 2013/2014 .Tujuan dari penelitian ini adalah untuk mengetahui pemanfaatan media pembelajaran sejarah berbasis audiovisual dalam pembelajaran sejarah, untuk mengetahui hasil belajar siswa kelas XI , dan pengaruh pemanfaatan media pembelajaran sejarah berbasis audio visual terhadap hasil belajar pada mata pelajaran sejarah siswa kelas XI IPS SMA N 2 Bae Kudus. Â  Â